Rheological test of flowability and diffusion behavior of carbon fibre reinforced polyamide - Nisa Naima Khalid,; Farhana Mohd Foudzi,; Ariffuddin Hasran,; Nabilah Afiqah Mohd Radzuan,; Abu Bakar Sulong, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Various materials have been produced to be used as feeder material in 3D printing application to obtain the level of mechanical properties and physical properties of a product. Before to its usage as a 3D printing feed material, polyamide-reinforced carbon fibre composites were investigated for flowability and diffusion behaviour. Using a heated nozzle to transform polymer filament into a semi-liquid that is extruded to create a structure layer-by-layer, the primary issue to prevent is delamination. For the success of this study, there are 2 main methods, namely to study the physical properties of carbon fibre reinforced polyamide composites against the composition of 20 wt.% carbon fibre and to study the temperature and rheological load on the rheological properties. Rheological test analysis found that the material flowability of 20 wt.% CF/PA at temperature parameters 210 °C, 230 °C and 250 °C against rheological loads (40, 60, 80) N recorded a range of viscosity values between 48.80 Pa.s to 97.88 Pa.s and shear rate value range between 19700 s-1 to 20270 s-1. Parameter optimization analysis using Taguchi method found that the largest factor contributing to the viscosity of CF/PA composite feed material was the addition of load applied. Moreover, the microstructural results of CF/PA composites show that smoother surfaces and good polymer structural bonding occur at an extrusion temperature of 250 °C. As a result, the rheology-derived flow rate may be used to tackle the problem of delamination and layer separation in 3D printing